Leadership Crisis Communication During the Pandemic of 2020 - Watkins, Daryl; Walker, Steven (Journal of Leadership, Accountability and Ethics, 2021)
COVID-19 provided a unique opportunity to examine leadership communication strategies during an extended crisis. The authors used political discourse analysis to review the crisis communication of President Donald Trump and seven U.S. governors using the U.S. Center for Disease Control crisis communication framework. The findings demonstrated that U.S. governors typically used effective communication strategies during their press briefings. President Trump often did not use effective crisis communication. The governors’ crisis communication styles were consistent with the CDC’s guidelines. The governors’ communication styles demonstrate that they are “in the arena,” while President Trump has attempted to remove himself from the arena.